CSF inflammatory biomarkers responsive to treatment in progressive multiple sclerosis capture residual inflammation associated with axonal damage. (June 2019) - Romme Christensen, Jeppe; Komori, Mika; von Essen, Marina Rode; Ratzer, Rikke; Börnsen, Lars; Bielekova, Bibi; Sellebjerg, Finn
Background: Development of treatments for progressive multiple sclerosis (MS) is challenged by the lack of sensitive and treatment-responsive biomarkers of intrathecal inflammation. Objective: To validate the responsiveness of cerebrospinal fluid (CSF) inflammatory biomarkers to treatment with natalizumab and methylprednisolone in progressive MS and to examine the relationship between CSF inflammatory and tissue damage biomarkers. Methods: CSF samples from two open-label phase II trials of natalizumab and methylprednisolone in primary and secondary progressive MS. CSF concentrations of 20 inflammatory biomarkers and CSF biomarkers of axonal damage (neurofilament light chain (NFL)) and demyelination were analysed using electrochemiluminescent assay and enzyme-linked immunosorbent assay (ELISA). Results: In all, 17 natalizumab- and 23 methylprednisolone-treated patients had paired CSF samples. CSF sCD27 displayed superior standardised response means and highly significant decreases during both natalizumab and methylprednisolone treatment; however, post-treatment levels remained above healthy donor reference levels. Correlation analyses of CSF inflammatory biomarkers and NFL before, during and after treatment demonstrated that CSF sCD27 consistently correlates with NFL. Conclusion: These findings validate CSF sCD27 as a responsive and sensitive biomarker of intrathecal inflammation in progressive MS, capturing residual inflammation after treatment. Importantly, CSF sCD27 correlates with NFL, consistent with residual inflammation after anti-inflammatory treatment being associated with axonal damage.